(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Drilling of wells is accompanied by pollution of all environmental components with drilling and process waste. With drilling operations carried out, terrain and soil mass disturbance occur first. Waste generated during the drilling process includes drilling muds, return drilling muds, drilling wastewater. The contaminating ability of drilling waste is determined by the use of chemical reagents and components involved in the preparation and processing of drilling muds. The use of additives and reagents is necessary to make sure the solution displays certain properties that ensure effective well drilling. The resulting waste is usually disposed of at landfills or is buried at the site of formation in mud pits, ensuring minimal environmental impact. The use of drill muds in other spheres is hindered by the complex composition of oily waste.The composition of liquid and solid fractions of drilling muds from several deposits were studied in laboratory setting. Waste samples were analyzed for moisture content, organic substances, oil products and other substances. According to the results of the research, measures for improving the properties of drilling muds were developed and proposed. For this purpose, an introduction of high sorption substances to the waste is proposed.The most effective should be the use of a sorbent capable of retaining organic matters and heavy metals. The resulting homogeneous soil-like mixture can be used for land reclamation in the city areas and other settlements, when performing planning works at the initial and final stages of construction, as well as at landscaping residential areas.